The auxiliary replicons of Butyrivibrio proteoclasticus : a thesis presented in fulfilment of the Doctorate of Philosophy degree at Massey University, Palmerston North, New Zealand - Yeoman, Carl (Massey University, 2009)
Butyrivibrio proteoclasticus B316T is the most recently described species of the Butyrivibrio / Pseudobutyrivibrio assemblage and now the first to have its genome sequenced. The genome of this organism was found to be spread across four replicons: a 3.5 Mb major chromosome and three additional large replicons: 186, 302 and 361 Kb in size. This thesis describes the sequencing, analysis, annotation and initial characterisation of all three B. proteoclasticus auxiliary replicons. Most significantly, these analyses revealed that the 302-Kb replicon is a second chromosome. This small chromosome, named BPc2, encodes essential systems for the uptake and/or biosynthesis of biotin and nicotinamide adenine mononucleotide, as well as the enzymes required for utilisation of fumarate as the terminal electron acceptor during anaerobic respiration, none of which are found on the main chromosome. In addition, BPc2 contains two complete rRNA operons, a large number of enzymes involved in the metabolism of carbohydrates, nitrogen and fatty acids. In contrast to BPc2, both megaplasmids appear largely cryptic, collectively encoding 421 genes not previously described in public databases. Nevertheless, only the 186-Kb, but not 361-Kb megaplasmid, could be cured from Butyrivibrio proteoclasticus B316T. The largest megaplasmid has a copy number of 5, while all other replicons are present at a copy number of 1. %GC content and codon usage analyses strongly suggests that all three auxiliary replicons have co-resided with the major chromosome for a significant evolutionary period. Moreover, the replication machineries of these three replicons are conserved. Interestingly, a survey of a number of Butyrivibrio / Pseudobutyrivibrio species revealed that the megaplasmids are widespread in this assemblage, however these other large plasmids do not show concordance with their 16S rRNA phylogeny and appear distinct to those of B. proteoclasticus B316T. A microarray analysis of gene expression in a co-culture experiment between B. proteoclasticus and the important ruminal methanogen, Methanobrevibacter ruminantium M1, revealed a potentially mutualistic interspecies interaction. In this relationship M. ruminantium appears to provide B. proteoclasticus with glutamate, essential to the final step of NAD+ biosynthesis, while B. proteoclasticus appears to provide M. ruminantium with formate, hydrogen and carbon dioxide, each important substrate for methanogenesis.
Keywords: Genetic sequencing; Replication; Butyrivibrio; Gene expression; Fields of Research::270000 Biological Sciences::270200 Genetics::270202 Genome structure